Three New Species of Salacia from Mesoamerica (Celastraceae, Salacioideae) - Lombardi, Julio Antonio [UNESP] (Missouri Botanical Garden, 2009)
Three new species of Salacia L. from Mesoamerica (Celastraceae, Salacioideae) are described from Panama. Salacia macrocremastra Lombardi is characterized by its very long pedicels to 50 mm, large flowers to 19 mm diam., and slightly bullate, elliptic leaves with a rounded base. Salacia mennegana J. Hedin ex Lombardi is distinguished by its buds with the calyx initially truncate and lobes that grow as the flower expands during anthesis, open inflorescences, annular disk, and ellipsoid fruits. Salacia partamensis Lumbardi can be recognized by its closed calyx with lobes that are irregular in bud and that tear apart as the flower opens, and its annular-pulvinate, slightly pentagonous disk with outer margin flattened.
Keywords: Celastraceae; IUCN Red List; Mesoamerica; Salacia; Salacioideae.